2018
DOI: 10.1111/ens.12331
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analysis reveals the importance of plant‐based diets for tropical ant‐mimicking spiders

Abstract: Ant‐mimicking spiders are a well‐known example of Batesian mimicry. Earlier studies have proposed that plant‐based diets (e.g. extrafloral nectar) are an important food source for ant‐mimicking spiders. However, it is still unclear whether the plant‐based diets are a main food source or supplementary energy source to the spiders. To examine the feeding habits, we measured stable nitrogen and carbon isotope ratios (δ15N and δ13C) of ant‐mimicking spiders (six species of Myrmarachne; one species of Agorius, Salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, our results suggest the possibility that Myrmarachne species changed their diets in nature or may have evolved specialized prey-capture behavior to compensate for the poor jumping ability. Although none of the field evidence indicated that Myrmarachne species have a specialized predation behavior, such as snatching prey from ants as observed in Menemerus jumping spiders 20 , our previous study using stable isotope analysis demonstrated that Myrmarachne species with slender body shapes, such as M. hashimotoi , had low δ 15 N values similar to those of nectar-feeding ants and arthropod herbivores, but not similar to those of predators, in the same study sites 21 . In contrast, the δ 15 N values of Myrmarachne species with broad body shapes, such as M. malayana and M. maxillosa , were similar to those of omnivorous ants and non-myrmecomorphic jumping spiders.…”
Section: Discussionmentioning
confidence: 68%
“…However, our results suggest the possibility that Myrmarachne species changed their diets in nature or may have evolved specialized prey-capture behavior to compensate for the poor jumping ability. Although none of the field evidence indicated that Myrmarachne species have a specialized predation behavior, such as snatching prey from ants as observed in Menemerus jumping spiders 20 , our previous study using stable isotope analysis demonstrated that Myrmarachne species with slender body shapes, such as M. hashimotoi , had low δ 15 N values similar to those of nectar-feeding ants and arthropod herbivores, but not similar to those of predators, in the same study sites 21 . In contrast, the δ 15 N values of Myrmarachne species with broad body shapes, such as M. malayana and M. maxillosa , were similar to those of omnivorous ants and non-myrmecomorphic jumping spiders.…”
Section: Discussionmentioning
confidence: 68%
“…Some spider species mimic ants in morphology or in chemical components on the body to feed on ants (Cushing 2012). Hyodo et al (2018) shows a result that δ 15 N values of A. hyodoi sp. nov. (as Agorius sp.…”
Section: Taxonomymentioning
confidence: 99%
“…Here, we address these questions using stable isotope analysis and DNA metabarcoding. Stable isotopes can be used to assess isotopic niche (Blüthgen et al, 2003; Hyodo et al, 2018; Newsome et al, 2007; Potapov et al, 2019). The heavier nitrogen isotope ( 15 N) is preferentially incorporated into tissues such that consumers have higher δ 15 N values than resources (Wada et al, 1991).…”
Section: Introductionmentioning
confidence: 99%